2023
DOI: 10.1038/s41408-023-00807-9
|View full text |Cite
|
Sign up to set email alerts
|

Multiple myeloma with t(11;14): impact of novel agents on outcome

Abstract: Multiple myeloma (MM) patients with t(11;14) present unique biological features and their prognosis is not well established. We report a retrospective study of 591 MM patients, 17.3% of whom had t(11;14). It was designed to determine the prognostic impact of this abnormality and the effect of novel agents on the response and outcomes. Three groups were established based on their cytogenetics: (1) t(11;14); (2) high-risk chromosomal abnormalities; and (3) standard risk (SR). After 80.1 months (1.2–273.8 months)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 46 publications
1
5
0
Order By: Relevance
“…In agreement with clinical findings of our study, Puertas et al (17) showed that greater people in the t (11;14) group had oligosecretory illness (although not substantially more) and more people had non-secretory disease (10.5 vs. 1.6%) compared to the SR group, while fewer people in the t (11;14) group had the IgA subtype (12.6 vs. 24.7%) or the light-chain kappa (51.6 vs. 63.6%). Blood calcium levels were higher in the t(11;14) group (9.97 mg/dL 1.36 vs. 9.62 mg/dL 1.37), and there was a decreased incidence of plasmacytomas (both paraskeletal and extramedullary types) in the t(11;14) group (17.2 vs. 38.6 percent).…”
Section: Resultssupporting
confidence: 94%
See 3 more Smart Citations
“…In agreement with clinical findings of our study, Puertas et al (17) showed that greater people in the t (11;14) group had oligosecretory illness (although not substantially more) and more people had non-secretory disease (10.5 vs. 1.6%) compared to the SR group, while fewer people in the t (11;14) group had the IgA subtype (12.6 vs. 24.7%) or the light-chain kappa (51.6 vs. 63.6%). Blood calcium levels were higher in the t(11;14) group (9.97 mg/dL 1.36 vs. 9.62 mg/dL 1.37), and there was a decreased incidence of plasmacytomas (both paraskeletal and extramedullary types) in the t(11;14) group (17.2 vs. 38.6 percent).…”
Section: Resultssupporting
confidence: 94%
“…Survival rates were considerably lower for patients with hypercalcemia and bone disease compared to people with anemia or renal failure. Puertas et al (17) found after a median follow-up of 80.1 months that 41.1% of patients were still living at the time of the last contact (range, 1.2-273.8 months).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…While direct comparison across trials is not feasible, it is evident that RRMM with high-risk cytogenetics does respond to POM + LD-Dex treatment. Thus, POM + LD-Dex appears to be efficacious for Chinese RRMM patients with high-risk cytogenetics and remains a favorable option for general RRMM patients, irrespective of high-risk cytogenetics [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%